PAPUA DALAM PERJALANAN SEJARAH NUSANTARA - Sinaga, Rosmaida; Alexander; Sihite, Dina; Lubis, Salsa Bila; Lubis, Yenny Maharani (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
Indonesia is an archipelagic country in which there are various ethnicities, cultures and histories. Society becomes a unified nation amidst ethnic, religious and cultural diversity. The diversity of the Indonesian nation should not be used as a reason for disintegration but rather as a cultural commitment to knowing, respecting and appreciating each other to strengthen and strengthen Indonesian unity. The historical journey of Papua and other ethnicities in the archipelago in the formation of Indonesia is important to explore to strengthen our unity and Indonesianness as a nation. The method used in this study is the historical method with heuristic, criticism or verification, interpretation and historiography stages. The research results show the historical journey of Papua in the context of the archipelago from the time of ancient kingdoms to the period of Dutch colonialism and the struggle for integration with Indonesia.